Determining a Solution In Exercises 23-30, determine whether the function is a solution of the differential equation xy' - 2y = x³ex, x > 0. 25. y = x²ex

Calculus: Early Transcendentals
8th Edition
ISBN:9781285741550
Author:James Stewart
Publisher:James Stewart
Chapter1: Functions And Models
Section: Chapter Questions
Problem 1RCC: (a) What is a function? What are its domain and range? (b) What is the graph of a function? (c) How...
icon
Related questions
Question
### Determining a Solution

In Exercises 23–30, determine whether the function is a solution of the differential equation:

\[ xy' - 2y = x^3e^x, \quad x > 0. \]

**25.** \( y = x^2e^x \)

**Explanation:**

To determine if \( y = x^2e^x \) is a solution to the differential equation, follow these steps:

1. **Differentiate \( y \):**

   Find \( y' \) by using the product rule. The product rule states that if you have a function \( y = u(x)v(x) \), then \( y' = u'v + uv' \).

   For \( y = x^2e^x \):

   - \( u = x^2 \) and \( v = e^x \)
   - \( u' = 2x \) and \( v' = e^x \)

   Applying the product rule, we get:

   \[
   y' = (2x)e^x + (x^2)(e^x) = e^x(2x + x^2)
   \]

2. **Substitute into the differential equation:**

   Substitute \( y \) and \( y' \) into the equation \( xy' - 2y = x^3e^x \).

   Left-hand side:

   \[
   xy' - 2y = x(e^x(2x + x^2)) - 2(x^2e^x)
   \]

   Simplifying:

   \[
   = xe^x(2x + x^2) - 2x^2e^x
   \]
   \[
   = x(e^x(2x) + e^xx^2) - 2x^2e^x
   \]
   \[
   = e^x(2x^2) + e^xx^3 - 2x^2e^x
   \]
   \[
   = x^3e^x
   \]

3. **Compare both sides:**

   The simplified left-hand side is \( x^3e^x \), which matches with the right-hand side of the original differential equation. Therefore, \( y = x^2e^x \) is indeed a
Transcribed Image Text:### Determining a Solution In Exercises 23–30, determine whether the function is a solution of the differential equation: \[ xy' - 2y = x^3e^x, \quad x > 0. \] **25.** \( y = x^2e^x \) **Explanation:** To determine if \( y = x^2e^x \) is a solution to the differential equation, follow these steps: 1. **Differentiate \( y \):** Find \( y' \) by using the product rule. The product rule states that if you have a function \( y = u(x)v(x) \), then \( y' = u'v + uv' \). For \( y = x^2e^x \): - \( u = x^2 \) and \( v = e^x \) - \( u' = 2x \) and \( v' = e^x \) Applying the product rule, we get: \[ y' = (2x)e^x + (x^2)(e^x) = e^x(2x + x^2) \] 2. **Substitute into the differential equation:** Substitute \( y \) and \( y' \) into the equation \( xy' - 2y = x^3e^x \). Left-hand side: \[ xy' - 2y = x(e^x(2x + x^2)) - 2(x^2e^x) \] Simplifying: \[ = xe^x(2x + x^2) - 2x^2e^x \] \[ = x(e^x(2x) + e^xx^2) - 2x^2e^x \] \[ = e^x(2x^2) + e^xx^3 - 2x^2e^x \] \[ = x^3e^x \] 3. **Compare both sides:** The simplified left-hand side is \( x^3e^x \), which matches with the right-hand side of the original differential equation. Therefore, \( y = x^2e^x \) is indeed a
Expert Solution
trending now

Trending now

This is a popular solution!

steps

Step by step

Solved in 2 steps with 2 images

Blurred answer
Recommended textbooks for you
Calculus: Early Transcendentals
Calculus: Early Transcendentals
Calculus
ISBN:
9781285741550
Author:
James Stewart
Publisher:
Cengage Learning
Thomas' Calculus (14th Edition)
Thomas' Calculus (14th Edition)
Calculus
ISBN:
9780134438986
Author:
Joel R. Hass, Christopher E. Heil, Maurice D. Weir
Publisher:
PEARSON
Calculus: Early Transcendentals (3rd Edition)
Calculus: Early Transcendentals (3rd Edition)
Calculus
ISBN:
9780134763644
Author:
William L. Briggs, Lyle Cochran, Bernard Gillett, Eric Schulz
Publisher:
PEARSON
Calculus: Early Transcendentals
Calculus: Early Transcendentals
Calculus
ISBN:
9781319050740
Author:
Jon Rogawski, Colin Adams, Robert Franzosa
Publisher:
W. H. Freeman
Precalculus
Precalculus
Calculus
ISBN:
9780135189405
Author:
Michael Sullivan
Publisher:
PEARSON
Calculus: Early Transcendental Functions
Calculus: Early Transcendental Functions
Calculus
ISBN:
9781337552516
Author:
Ron Larson, Bruce H. Edwards
Publisher:
Cengage Learning